Efektivitas Konseling Rasional Emotive Behavior Therapy (REBT) Untuk Meningkatkan Kesehatan Mental Mahasiswa - Apriyanto, Tomy Dwi; Fanisa, Nurul; Dwi Rahayu, Endang (Jurnal Paedagogy, 2022)
This study aims to analyze the effectiveness of rational emotive behavior therapy (REBT) counseling to improve the mental health of students of the BK Uhamka study program in 2021. The method used in this study was a quasi-experimental one group pretest-posttest design. The approach used in this research is a quantitative approach. The number of samples in this study amounted to 11 students of UHAMKA counseling guidance in 2021 with sampling using the purposive sampling method. This research instrument uses a questionnaire. As for the data analysis technique using the Wilcoxon T test. The results of this study indicate that the Wilcoxon T test with calculations using SPSS ver. 26 prove simp. Sig. (2-tailed) = 0.003. Because the value is 0.003 <0.05, so Ho is rejected, in other words there is a significant effect before and after giving the pretest-posttest. So it can be concluded that group counseling services using REBT techniques are effective in improving students’ mental health. It can be seen from the 11 students who took counseling with the REBT technique that their pretest and posttest scores increased or in other words experienced changes after being given counseling services with the REBT technique.